2024
DOI: 10.7589/jwd-d-23-00077
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma Gondii Infection in the Eurasian Beaver (Castor Fiber) in Switzerland: Seroprevalence, Genetic Characterization, and Clinicopathologic Relevance

Patrick Scherrer,
Marie-Pierre Ryser-Degiorgis,
Caroline F. Frey
et al.

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…However, several studies have reported differences in T. gondii infection in small mammals from different highly anthropised areas in Europe [ 7 , 18 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] ( Table 1 ), suggesting different rates of exposure to the parasite associated with specific factors from the studied areas (i.e., environmental conditions, host communities, host susceptibility, T. gondii lineages).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have reported differences in T. gondii infection in small mammals from different highly anthropised areas in Europe [ 7 , 18 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] ( Table 1 ), suggesting different rates of exposure to the parasite associated with specific factors from the studied areas (i.e., environmental conditions, host communities, host susceptibility, T. gondii lineages).…”
Section: Discussionmentioning
confidence: 99%
“…In urban areas, feral cat populations reach high densities, increasing the probability of T. gondii transmission between hosts [ 5 ]. From this perspective, recent studies have shown significant positive associations between human population density and T. gondii oocysts shedding in domestic and wild felids [ 5 ] and seroprevalence in wild mammals [ 4 , 6 , 7 ]. Therefore, urbanisation may create ideal environmental conditions for the ecology of this parasite [ 5 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%